2017
DOI: 10.1002/2016jd026385
|View full text |Cite
|
Sign up to set email alerts
|

Microseepage of methane to the atmosphere from the Dawanqi oil‐gas field, Tarim Basin, China

Abstract: The microseepage of natural gas from subsurface hydrocarbon reservoirs is a widespread process in petroleum basins. On a global scale, microseepage represents an important natural source of atmospheric methane (CH4). To date, microseepage CH4 flux data have been obtained from ~20 petroleum systems in North America, Europe, and Asia. While the seasonal variations of gas flux due to soil methanotrophic activity are known, the role of geological factors in controlling gas fluxes has been poorly investigated. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…The microseepage database of Etiope and Klusman [26] shows that, statistically, positive fluxes occur in less than 50% of a petroleum field's area, and there are three possible levels of microseepage. Based on this, total methane emissions to the atmosphere in the Dawanqi field were evaluated be on the order of 60 t/yr [27]. Negative fluxes are a consequence of methanotrophic activity when the speed of diffusion and infiltration of methane from the oil reservoir is lower than that of its methanotrophic oxidation activity.…”
Section: Resultsmentioning
confidence: 99%
“…The microseepage database of Etiope and Klusman [26] shows that, statistically, positive fluxes occur in less than 50% of a petroleum field's area, and there are three possible levels of microseepage. Based on this, total methane emissions to the atmosphere in the Dawanqi field were evaluated be on the order of 60 t/yr [27]. Negative fluxes are a consequence of methanotrophic activity when the speed of diffusion and infiltration of methane from the oil reservoir is lower than that of its methanotrophic oxidation activity.…”
Section: Resultsmentioning
confidence: 99%
“…One of these has been adapted to and coupled with a flux chamber. Tang et al [35] reported CH 4 seepage measurements using this instrument at the Dawanqi and Yakela oil fields. This will result in a substantial increase in speed and sensitivity of flux measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The previously published global microseepage data set contains 1,509 measurements from 10 hydrocarbon basins (Table 3; Klusman et al, 2000;Klusman, 2003;Etiope, 2005;Klusman, 2005;Etiope et al, 2006;LT Environmental, 2007;Tang et al, 2007;Etiope & Klusman, 2010;Tang et al, 2010Tang et al, , 2017. Sampled areas are primarily in Western United States, Italy, and Northwest China, with a few additional measurements in Romania and Greece, leaving most of the world's hydrocarbon basins unrepresented in the global data set.…”
Section: Background and Motivationmentioning
confidence: 99%